Formate as Anti‐Oxidation Additives for Pb‐Free FASnI3 Perovskite Solar Cells. Issue 12 (17th October 2022) - Jang, Hyungsu; Lim, Hyeong Yong; Yoon, Yung Jin; Seo, Jongdeuk; Park, Chan Beom; Son, Jung Geon; Kim, Jae Won; Shin, Yun Seop; An, Na Gyeong; Choi, Seung Ju; Kim, Su Hwan; Jeong, Jaeki; et al.
Abstract : Pb‐free Sn‐based perovskite solar cells (PSCs) have significant potential for application in photovoltaic devices because of their suitable bandgap, low exciton binding energy, high carrier mobility, and long diffusion length. However, their performance is hampered by several issues. Sn‐based perovskites are highly susceptible to oxidation, which induces a high concentration of defects and degrades the chemical stability of the perovskite crystals. Herein, the anion formate (HCOO − ) can effectively suppress the oxidation of Sn in the pure formamidinium tin triiodide (FASnI3 ) perovskite without using A‐site cationic additives. Moreover, the presence of formate results in a uniform pinhole‐free perovskite film with a low trap density, reduced charge carrier recombination, and improved charge extraction. Density functional theory calculations show that formate‐treated FASnI3 has improved stability against oxidative Sn degradation. The formate‐treated PSC achieves a power conversion efficiency of 12.11% at a high open‐circuit voltage of 0.71 V. The device exhibits improved stability in ambient air in which it maintained over 80% of its initial power conversion efficiency after 180 min because oxidation is inhibited owing to the strong interaction between Sn and formate. Abstract : The formate effectively suppressed oxidation through the coordinate bond to Sn. According to the density functional theory calculation, the formate interferes with the hydrogen bonding of FA + and O2, and the adsorption affinity is reduced. Comprising enhanced morphology with pinhole free, and a decrease of nonradiative recombination and trap density of perovskite film, the high‐efficiency Pb‐free FASnI3 perovskite solar cells are successfully fabricated.